(untitled) (Research, Society and Development, 2020)
This work has the objective to discuss the hypotheses about the origin of life with an emphasis on classical experiments on spontaneous generation and biogenesis from a study which renders the student protagonist in the process of teaching-learning about the theme. The study presents questions that are novel and the text was drawn from the textbook used by students. It was applied in a room on the 1st year of secondary education in a public school in Barra Mansa, during the Biology classes. With the application of study, we noted that a more active attitude of students who showed interest in the construction of scientific knowledge about the proposed theme.